Construction of 3D Polymer Brushes by Dip‐Pen Nanodisplacement Lithography: Understanding the Molecular Displacement for Ultrafine and High‐Speed Patterning. Issue 5 (25th September 2014) - Chen, Chaojian; Zhou, Xuechang; Xie, Zhuang; Gao, Tingting; Zheng, Zijian
<x xml:space="preserve">Abstract</x> Dip‐pen nanodisplacement lithography (DNL) is a versatile scanning probe‐based technique that can be employed for fabricating ultrafine 3D polymer brushes under ambient conditions. Many fundamental studies and applications require the large‐area fabrication of 3D structures. However, the fabrication throughput and uniformity are still far from satisfactory. In this work, the molecular displacement mechanism of DNL is elucidated by systematically investigating the synergistic effect of z extension and contact time. The in‐depth understanding of molecular displacement results in the successful achievement of ultrafine control of 3D structures and high‐speed patterning at the same time. Remarkably, one can prepare arbitrary 3D polymer brushes on a large area (1.3 mm × 1.3 mm), with <5% vertical and lateral size variations, and a patterning speed as much as 200‐fold faster than the current state‐of‐the‐art.